Designing an Economic Valuation Model of the Intangible Assets of Volleyball Clubs in Iran - Mohammad Ali Sahebkaran; Mahdi Talebpour; Mohammad Keshtidar; Mohammad Ghorbani (The Society of Aging and Physical Activity (SAPA), 2019)
Background. Several studies have been conducted on the valuation of the intangible assets of organizations not relating to sport. However, there is no comprehensive study in the sport organizations especially in Iran. It is not clear what criteria are required at different levels by the sport organizations especially volleyball clubs to evaluate their intangible assets. Objectives. In spite of the increasing importance of the intangible assets in various industries, little has been done on the identification of the underlying factors and valuation of this category of assets in sport industry. Therefore, the purpose of this study was to design an economic valuation model of the intangible assets of the volleyball clubs in Iran. Methods. The sample of the present study in the qualitative section consisted of 47 subjects with 600 subjects participating in the quantitative section. Through application of Cochran formula, the sample size was estimated to be 234 subjects. The study was conducted in a survey method. To this end, first, the intangible assets of the Iranian volleyball clubs were identified using a qualitative method and then analyzed through structural equation modeling (SEM) PLS3 and SPSS22. Results. The factors with the greatest effects on economic valuation of intangible assets of Iranian volleyball clubs were communication capital, spiritual capital, structural capital and human capital. Thus, it was found that in the economic valuation of intangible assets of Iranian volleyball clubs, the indices such as the relationship between investors and partners and their loyalty in communication capital had the highest value among other indices. Further, the club history and success had the same status in promoting spiritual capital, governing culture of the club, development outlook document of the club in the structural capital, management of contracts, and the number of national players in the club in human capital. Conclusion. The results of the present study suggested that the proposed conceptual model can be applied by researchers, administrative and financial managers of volleyball clubs and the experts of the privatization organization to have a more comprehensive and precise evaluation of the valuation of intangible assets of a club.